2021
DOI: 10.1016/j.ebiom.2021.103561
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of antibody responses up to 13 months after SARS-CoV-2 infection and risk of reinfection

Abstract: Background: Assessment of the kinetics of SARS-CoV-2 antibodies is essential in predicting risk of reinfection and durability of vaccine protection. Methods: This is a prospective, monocentric, longitudinal, cohort clinical study. Healthcare workers (HCW) from Strasbourg University Hospital were enrolled between April 6th and May 7th, 2020 and followed up to 422 days. Serial serum samples were tested for antibodies against the Receptor Binding Domain (RBD) of the spike protein and nucleocapsid protein (N) to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
176
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(208 citation statements)
references
References 33 publications
29
176
1
2
Order By: Relevance
“…Data on the persistence of the SARS-CoV-2-specific immune response are of great importance for managing the pandemic and planning further measures for increasing the population's resistance to the virus. To date, both sero-epidemiological and targeted cohort studies from different countries have reported detectable levels of virus-specific antibodies and duration of the protective immune response from 3 to 13 months after infection [6,7,10,12,13,17,19,21,24,25]. Previous cohort studies on the formation and persistence of SARS-CoV-2-specific humoral immune response mainly included healthcare workers as a target group having the highest risk of being exposed to SARS-CoV-2 [13,14,16,19,20,24,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the persistence of the SARS-CoV-2-specific immune response are of great importance for managing the pandemic and planning further measures for increasing the population's resistance to the virus. To date, both sero-epidemiological and targeted cohort studies from different countries have reported detectable levels of virus-specific antibodies and duration of the protective immune response from 3 to 13 months after infection [6,7,10,12,13,17,19,21,24,25]. Previous cohort studies on the formation and persistence of SARS-CoV-2-specific humoral immune response mainly included healthcare workers as a target group having the highest risk of being exposed to SARS-CoV-2 [13,14,16,19,20,24,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in virus-specific antibody levels is observed at days 16-35 after the onset of symptoms [4,[7][8][9][10]. Some studies have reported that antibody levels peak within the first few months, then wane and remain stable for several months, indicating that the immunity may last longer [4,8,[10][11][12][13][14][15][16]. Other studies suggest that the levels of SARS-CoV-2-specific IgG are durable and decline after 6-8 months while the number of memory B cells increases within 8 months after infection [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longevity of serum-IgA post infection varies between different studies: seroreversion has been observed within 3 months (9,12), though other studies have shown that IgA may remain detectable over 6 months and up to a year post infection (13-18). Serum-IgA appears earlier than serum-IgG, but has been observed to be less long-lasting than serum-IgG post infection (9,12,15,19). Serum-IgG is considered the clinical standard serological assay for detection of past infection and has been shown present up to 13 months post infection (19).…”
Section: Introductionmentioning
confidence: 99%
“…Serum-IgA appears earlier than serum-IgG, but has been observed to be less long-lasting than serum-IgG post infection (9,12,15,19). Serum-IgG is considered the clinical standard serological assay for detection of past infection and has been shown present up to 13 months post infection (19). However, as the sensitivity and specificity of different IgG-assays targeting the different viral structures vary, seroconversion in commercial IgG assays may be difficult to interpret in the absence of PCR testing and in asymptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%